Association of peripheral CD8+ T cell activation with disease activity and treatment resistance in systemic lupus erythematosus - Yoshiya Tanaka; Hiroaki Tanaka; Satoshi Kubo; Yuya Fujita; Shingo Nakayamada; Yusuke Miyazaki; Koshiro Sonomoto (RMD Open)
Objective Various immune-cell subsets intricately mediate the pathogenesis of systemic lupus erythematosus (SLE). However, the role of CD8+ T cells in SLE remains unclear. We investigated the proportions and characteristics of peripheral CD8+ T cells and their association with clinical manifestations of SLE.Methods We retrospectively enrolled 211 patients with SLE and 48 age- and sex-matched healthy controls (HCs). Peripheral CD8+ T cells were analysed using flow cytometry. The primary endpoint was the comparison of peripheral CD8+ T cell subset characteristics between patients and HCs.Results Patients with SLE (mean age, 42.3 years; women, 89% and mean disease duration, 112.8 months) had significantly higher proportions of naïve CD8+ T cells (CCR7+CD45RA+), CD8+ terminally differentiated effector memory cells (CCR7−CD45RA+) and activated CD8+ T cells (CD38+HLA-DR+) in peripheral blood mononuclear cells than HCs (p<0.001). Activated CD8+ T cells produced granzyme B and interferon-γ, which correlated with serum double-stranded (ds) DNA antibodies (rs=0.3146, p<0.0001) and 50% haemolytic unit of complement (rs=−0.3215, p=0.0003), and were significantly increased in patients with active systemic, renal or haematological involvement (p<0.05). Cluster analysis-based subgroup classification based on CD8 cell differentiation and activation revealed a group with high numbers of activated CD8+ T cells, highly active SLE and organ damage, including active nephritis and persistently high cell counts after a 24-week treatment, indicating treatment resistance (high anti-dsDNA antibody titres and high glucocorticoid doses).Conclusion In SLE, greater proportions of highly cytotoxic and proinflammatory activated CD8+ T cells in peripheral blood-modulated disease activity, organ damage and residual treatment resistance, presenting a potential treatment target.